Patricia Stamp. Technology, gender and power in Africa. Ottawa : International Development Research Centre, 1989. 185 p. (Technical study, 63e) - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1990)
PATRICIA STAMP, Technology, gender and power in Africa, Technical Study 63e, International Development Research Centre, Ottawa, 1989.